Representing the Jewishness of Christ Jesus in Children’s Books - von Kellenbach, Katharina (Studies in Christian-Jewish Relations, 2026)
Anti-Judaism has long shaped the perception and illustration of Jews and Judaism in Christian art history. Despite recent progress to retire the “Aryan Jesus,” there is not yet consensus on how to teach a “Jewish Jesus” to Christian children. Children’s books are steeped in historical realism and literalism that present Jews primarily in the role of enemies of Jesus. A recent German children’s book experiments with different visual and textual strategies to make the Jewishness of Jesus meaningful to Christian children.